2015
DOI: 10.18632/oncotarget.4275
|View full text |Cite
|
Sign up to set email alerts
|

Detecting cell-in-cell structures in human tumor samples by E-cadherin/CD68/CD45 triple staining

Abstract: Although Cell-in-cell structures (CICs) had been documented in human tumors for decades, it is unclear what types of CICs were formed largely due to low resolution of traditional way such as H&E staining. In this work, we employed immunofluorescent method to stain a panel of human tumor samples simultaneously with antibodies against E-cadherin for Epithelium, CD68 for Macrophage and CD45 for Leukocytes, which we termed as “EML method” based on the cells detected. Detail analysis revealed four types of CICs, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 26 publications
2
58
0
Order By: Relevance
“…For instance, Huang et al identified four subtypes of CICs which could be formed homotypically among tumor cells or heterotypically between tumor cells and leukocytes. They also stated that macrophages could target live tumor cells to generate CICs [12]. As mentioned above, entosis is described a nonapoptotic cell death program in matrix-detached cells initiated by the invasion of one living cell into another [5].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Huang et al identified four subtypes of CICs which could be formed homotypically among tumor cells or heterotypically between tumor cells and leukocytes. They also stated that macrophages could target live tumor cells to generate CICs [12]. As mentioned above, entosis is described a nonapoptotic cell death program in matrix-detached cells initiated by the invasion of one living cell into another [5].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MIF and CD68 can be used as markers to detect both M1 and M2 macrophages and reveal macrophage expression of the burninjury site [73,74]. After HBO treatment, the expression of TNF-α and IL-1β significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on samples from six types of human tumors, Huang et al [4] analyzed the cell types involved in CICs in human tumors by the "EML" method, where immunofluorescent staining was performed with antibodies against E-cadherin, CD68 and CD45 for Epithelium, Macrophage and Leukocytes (EML), respectively. Consistent with the above classification, they identified both homotypic and heterotypic CICs, whose amounts were comparable (54% vs 46%).…”
Section: Research Highlightmentioning
confidence: 99%
“…Meanwhile, tumor-associated macrophages (TAM), a sub-population of macrophages derived from bone marrow, were found important players in tumor progression by influencing multiple processes including angiogenesis, tumor cell invasion, intravasation, extravasation and persistent growth and the like [3] . Recently, macrophages were demonstrated to be involved in the formation of a type of unique cellular structures called cell-in-cell structures (CICs) in human tumor samples [4] , which refreshes our views on the roles of macrophages in tumor biology and potentially provide a novel target for tumor therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation